Do outro lado do altar : padres casados e militância católica - Brentan, Marcelo Fernandes (2017)
This research studies by Oral History of Life, recordkeeping and theoretical procedures of sociology of religion, the political actions of married priests and their wives from the Administrative Institute of Jesus the Good Shepherd (IAJES) in the context of the military dictatorship between 1970 and 1985, under influence of the Liberation`s Theology, and the operation of the base ecclesial communities (BECs), between its begginig and endind period (1969-1996) in the Alto Paraná region, in the cities of Andradina-SP and Três Lagoas-MS, organizing and constituting religious and politic militancy in the region and in Brazil in the past, and currently remains through branches as the Married Priests Movement of Brazil (MPC). For this we analyzed the organizational structure of IAJES and MPC, its operation and how do they positioned in front of the church`s symbolism in relation to married priests and their wifes. Thus, we analyze the break with clerical celibacy imposed by the priestly-traditional catholic power and its legitimation and distinctions in contemporary Brazil.